Pengaruh Kompos Limbah Kulit Kopi (Coffea) Terhadap Pertumbuhan Tanaman Kacang Panjang (Vigna sinensis L.) - Hartati Hartati; Nikman Azmin; Andang Andang; Muhammad Eka Hidayatullah (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
This study aims to determine the effect of coffee skin waste compost on the growth of long beans (Vigna sinensis L.). This study uses a completely randomized design (CRD). Data analysis using ANOVA test. The results of the research showed that the growth of Vigna sinensis L. after being given coffee waste skin compost fertilizer was an average plant height and number of leaves after 2 weeks, 4 weeks and 6 weeks, ie with a dose of treatment A1 (33.00 cm and 19 strands), A2 ( 48.90 cm and 25 strands), A3 (61.27 cm and 3 strands) and A4 (61.27 cm and 3 strands). While the results of the analysis of the value of Fcount and Ftable from the high growth of Vigna sinensis L.. showed at age 2 weeks 8.13 > 4.07, 4 weeks 7.99 > 4.07, and 6 weeks 14.34 > 4.07. While the results of the analysis of the value of Fcount and Ftable from most of the leaves of Vigna sinensis L. at the age of 2 weeks 17.00 > 4.07, 4 weeks 7.58 > 4.07, and 6 weeks 6.44 4.07. The use of coffee skin waste compost fertilizer can increase the high growth and number of leaves of the Vigna sinensis L.. plant.